Development of Colloid System Electronic Module Based On Problem Solving Integrated Ethnochemistry for High School Students - Alvin Nur Zahro; Woro Sumarni; Cepi Kurniawan (International Conference on Science, Education, and Technology, 2022)
Abstrak. The colloid system is one of the chemical materials that contains many concepts and is related to everyday life, so that students still find it difficult to understand. The aim of this research is to evolve a module electronic based on problem solving integrated ethnochemistry on colloid system. The exploration method applied is Research and Development (R & D) with a 4D research design modified into 3D (define, design, and develop). Data was collected using interview techniques, expert validation, user response questionnaires, and implementation observation sheets. The results of the feasibility assessment by the expert validator were 86.73% with a very feasible category. The results of the readability, practicality, and student answers to the e-module each attained a score of 87.9%; 91.3%; and 86.9% in the veritably practicable category. The results of the learning implementation test using the e-module obtained a score of 96.4% in the very well implemented category. The conclusion of this exploration is that the expansion of an e-module based on problem solving integrated ethnochemistry is very feasible to use and gets a positive response by users to the e-module that has been evolved.